Atomically thin WS2 nanosheets based gas sensor - Late, D. J.; Kanawade, R. V.; Kannan, P. K.; Rout, C. S. (Sensor Letters, 2016)
We report here the UV light and NO2 gas sensing properties of atomically thin few-layered WS2 nanosheets synthesized by a simple hydrothermal method. For the UV sensor, the response time was observed to be <15 s whereas the recovery time was <56 s. The Few layered WS2 nanosheets sensor devices were also tested for different concentration of NO2 gas at room temperature and 100 °C. The response time was observed to be <60 s whereas recovery time was >10 min. Further, the response and recovery time can be shortened by UV illumination or by removing the absorbed gas by heating the device at higher temperature. Our results open up the new avenues for gas sensors based on two-dimensional inorganic layered materials.

Synergistic MoS2@MWCNT nanocomposites for high-efficiency catalysis and energy applications - Auti, P. S.; Kanawade, R. V.; Alshehri, S. A.; Warule, S. S.; Shin, D. K.; Yewale, M. A. (Chemical Physics Letters, 2025)
The MoS2-MWCNT composite heterojunction for its potential as an electrocatalyst and energy storage material. The composite demonstrated remarkable electrochemical performance, achieving a specific capacitance of 263 F/g, an energy density of 16.89 Wh/kg, and a power density of 478 W/kg. Using CV profiles, we analyzed the charge storage mechanism and found that the anodic and cathodic processes had b values of 0.48 and 0.45, respectively, indicating diffusion-controlled behavior. Diffusion coefficients of 6.44 x 10(-7) cm(2)/s (anodic) and 11.32 x 10(-7) cm(2)/s (cathodic) confirmed this mechanism. In the constructed device using MoS2-MWCNT and activated carbon (AC), we observed a specific capacitance of 18.71 F/g, an energy density of 5.09 Wh/kg, and a power density of 833 W/kg. After stability, testing, electrochemical impedance spectroscopy (EIS) revealed a slight increase in series resistance, rising from 2.33 Omega to 2.49 Omega. The MoS2-MWCNT composite also exhibited excellent electro catalytic performance. For the hydrogen evolution reaction (HER), it achieved an over potential of 0.221 V and a Tafel slope of 0.321 V/dec. After stability testing, we measured Rs and Rct values of 4.86 Omega and 2.57 Omega, respectively. For the oxygen evolution reaction (OER), the composite showed an over potential of 597 mV and a Tafel slope of 0.285 V/dec, with post-stability Rs and Rct values of 5.63 Omega and 5.57 Omega, respectively. These findings highlight the versatility of the MoS2-MWCNT composite for applications in energy storage and water splitting.
Keywords: electrocatalysis; hydrothermal; MoS2-MWCNT; supercapacitor; TEM; XPS